24➗2.88=0.8
30➗0.8 = 3.75
So the answer is 3.75
6(x +y) -(a +b) = 6(-5) -(-5)
= -25
Answer:
option A
12m/s
Step-by-step explanation:
Given in the question,
mass of object = 11kg
kinetic energy possess by = 792 joules
To find the velocity we use formula
v = ![\sqrt{\frac{2KE}{m} }](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7B2KE%7D%7Bm%7D%20%7D)
Plug values in the formula
v = ![\sqrt{\frac{2(792)}{(11)} }](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7B2%28792%29%7D%7B%2811%29%7D%20%7D)
v = ![\sqrt{\frac{1584}{11} }](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cfrac%7B1584%7D%7B11%7D%20%7D)
v = ![\sqrt{144}](https://tex.z-dn.net/?f=%5Csqrt%7B144%7D)
v= 12 m/s
42 / 38x
This sentence is just to fill up space.